The practice of fair value accounting in Singapore - Liew, Siow Hwei (2014)
Traditionally, the objective of accounting is to report on how well a steward was managing the resources entrusted to him. However, there is a shift in emphasis in financial reporting from stewardship to decision making usefulness. With this shift, fair value accounting has grown in importance.